2013
DOI: 10.1158/0008-5472.can-11-3635
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Control by the VEGF-C/NRP-2 Axis in Cancer and Its Implication for Treatment Resistance

Abstract: A major contributor to cancer mortality is recurrence and subsequent metastatic transformation following therapeutic intervention. Therefore, in order to develop new treatment modalities and improve the efficacy of current ones, it is important to understand the molecular mechanisms that promote resistance to therapy in cancer cells. One pathway contributing to therapy resistance is autophagy, a self-digestive process that can eliminate unnecessary or damaged organelles to protect cancer cells from death. We h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 51 publications
3
97
0
Order By: Relevance
“…30,31 In a breast cancer model, a similar antioxidant function of VEGF-C/NRP2 was observed. However, in this study, superoxide dismutase 3 was identified as the principal mediator.…”
Section: Vegf-c and Neurophilinmentioning
confidence: 65%
“…30,31 In a breast cancer model, a similar antioxidant function of VEGF-C/NRP2 was observed. However, in this study, superoxide dismutase 3 was identified as the principal mediator.…”
Section: Vegf-c and Neurophilinmentioning
confidence: 65%
“…The autophagic flux can be reflected by the fold change in LC3-II levels with or without chloroquine. 10,11 We found that the fold change in LC3-II levels in cisplatin-resistant A2780/CP70 cells after lysosome inhibition via chloroquine was remarkably upregulated in response to cisplatin treatment, suggesting autophagy induction (Fig. 1A).…”
Section: Cisplatin Induces Autophagic Flux In Cisplatin-resistant Ovamentioning
confidence: 93%
“…However, this study did not investigate the contribution of specific NRP ligands and it is therefore not known if the mechanism is VEGF dependent. VEGF may also regulate autophagy because it has been shown that NRP2-mediated VEGFC signalling mediated by mTOR complex 1 activates an autophagic mechanism that combats chemotherapy-induced stress, which has implications for the role of VEGF signalling in therapy resistance 93 .…”
Section: Vegf-mediated Functions In Tumour Cellsmentioning
confidence: 99%